The Social Context and Meaning of Virginity Loss among African American and Puerto Rican Young Adults in Hartford. (18th September 2013) - Erickson, Pamela I.; Badiane, Louise; Singer, Merrill
<x xml:space="preserve">Abstract</x> We describe virginity loss experiences of inner‐city minority youth to understand the meaning attributed to first sex and the social and structural factors that contribute to early sexual debut. We interviewed 62 18–25‐year‐old African American and Puerto Rican Hartford men and women about their sexual and romantic life histories. Transcripts were coded in ATLAS.ti and analyzed for themes about virginity and sexual debut. We found different conceptions of virginity as a stigma to be lost, a normal part of growing up, and a gift to be given. The normative experience was consensual, early, and unplanned sexual debut. Inner‐city minority youth have similar feelings, motivations, and experiences of sexual debut as non‐ethnic youth reported in the literature except they are far younger. We discuss structural factors that affect inner‐city sexual scripts for early sexual debut and identify it as a health inequity.